2017
DOI: 10.15583/jpchrom.2017.008
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Water-Insoluble and Neutral Linear Synthetic Polymers in Nonaqueous Capillary Zone Electrophoresis Using Phosphonium-Based Ionic Liquid

Abstract: The separation of neutral and water-insoluble linear synthetic polymers in non-aqueous capillary zone electrophoresis using the hydrophobic phosphonium-based ionic liquid trihexyl(tetradecyl)phosphonium chloride (P 66614 Cl) were investigated using polystyrene, polymethylmethacrylates, polybutadiene, and polycarbonate as test analytes. The solubility of P 66614 Cl in tetrahydrofuran was above 500 mM, which was significantly higher than that of the general ionic surfactants used in our previous studies. The sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In this case, both nylons were coeluted with HFIP containing 400 mM CTAC. In a previous investigation, we found that the use of hydrophobic cations is effective for enhancing polymer separation [14]. Therefore, phosphonium-based ionic liquid (P66614Cl) was employed as a cationic reagent to generate electrophoretic force of the polymers instead of CTAC.…”
Section: Electrophoresis Of Polyesters and Polyamides In Hfip Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, both nylons were coeluted with HFIP containing 400 mM CTAC. In a previous investigation, we found that the use of hydrophobic cations is effective for enhancing polymer separation [14]. Therefore, phosphonium-based ionic liquid (P66614Cl) was employed as a cationic reagent to generate electrophoretic force of the polymers instead of CTAC.…”
Section: Electrophoresis Of Polyesters and Polyamides In Hfip Mediamentioning
confidence: 99%
“…In subsequent studies, we investigated the effect of surfactant species and electrophoretic medium compositions on electrophoretic behaviors using THF-based electrophoretic media [13][14][15]. Specifically, synthetic polymers soluble in THF were used as test analytes for these investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The apparatus and procedure were similar to those described in our previous study [15]. A commercial CAPI-3100 instrument (Otsuka Electronics, Osaka, Japan) with a fused-silica capillary of i.d.…”
Section: Apparatus For Naczementioning
confidence: 99%
“…Recently, we reported the separation of water-insoluble synthetic polymers in NACZE, in which a THF-based organic solution containing ionic surfactants was used as the electrophoretic media [13][14][15]. In this case, the THF-based solution was employed to make the nonionic and water-insoluble polymers dissoluble.…”
Section: Introductionmentioning
confidence: 99%
“…Capillary electrophoresis (CE) is an effective tool for evaluating the interaction between the compounds in the liquid phase [8][9][10][11][12]. Therefore, we employed CE to evaluate the interactions between the metals and micelles in the presence of hydrophobic extraction agents.…”
Section: Introductionmentioning
confidence: 99%